Partnering with local industries to drive STEM engagement: A solar energy case study in West Virginia - McDaniel, Angela (American Journal of STEM Education, 2025)
This paper explores the integration of local industry partnerships to enhance STEM education in rural middle schools through renewable energy education. By collaborating with a regional solar grid and battery storage company, students engaged in hands-on lessons using Snap Circuits® kits to explore electricity, solar power, and energy grid design. Students designed and connected solar-powered model homes to simulate a solar grid network. These activities fostered critical thinking, systems thinking, and collaborative problem-solving, making STEM careers tangible and accessible. This study highlights the importance of leveraging local industries to create authentic, place-based STEM experiences that foster career awareness, deepen understanding, and enhance student engagement.